2023
DOI: 10.1093/g3journal/jkad116
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and phenomics enabled prebreeding improved early-season chilling tolerance in Sorghum

Abstract: In temperate climates, earlier planting of tropical-origin crops can provide longer growing seasons, reduce water loss, suppress weeds, and escape post-flowering drought stress. However, chilling sensitivity of sorghum, a tropical-origin cereal crop, limits early planting, and over 50 years of conventional breeding has been stymied by coinheritance of chilling tolerance (CT) loci with undesirable tannin and dwarfing alleles. In this study, phenomics and genomics-enabled approaches were used for prebreeding of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To ensure the quality of the data, a subset of samples was genotyped in duplicate, and the genotyping results were compared to ensure consistency. In addition, a set of positive and negative control samples were included in each genotyping run to monitor the performance of the reaction and to assess the accuracy of the genotyping results [5].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the quality of the data, a subset of samples was genotyped in duplicate, and the genotyping results were compared to ensure consistency. In addition, a set of positive and negative control samples were included in each genotyping run to monitor the performance of the reaction and to assess the accuracy of the genotyping results [5].…”
Section: Discussionmentioning
confidence: 99%
“…QTL mapping has been used in sorghum to study genomics and phenomics. For example, a study utilized a chilling nested association mapping population with 43 K GBS SNPs and uncrewed aircraft system (UAS) high-throughput phenotyping to provide high-resolution chilling tolerance (CT) mapping, addressing weak trait-to-QTL association from previous sorghum CT studies (Marla et al 2023) Similarly, a genome-wide association study (GWAS) identified causal polymorphisms for traits like drought tolerance and biomass yield based on historical recombination events in sorghum by employing a drone (Spindel et al 2018). The drone was a modified multirotor vehicle with Blue River's proprietary imaging payload (Spindel et al 2018).…”
Section: Studying the Genetic Basis Of Complex Traitsmentioning
confidence: 99%